UCE Program and 3D Students Development - Isa, Khairunesa; Zaky Noh, Mohamad; Sarawati Johar, Siti; Md Yusoff, Rosman; Rahman Ahmad, Abd (International Journal of Engineering and Technology, 2018)
The purpose of this study is to evaluate the impact of the application of University Community Engagement (UCE) on the development of 3D students of Universiti Tun Hussein Onn Malaysia. A total of 10 students from various fields of study who are in the background of engineering flow have joined UCE. This review is more emphasis on the consistency of the elements contained in the UCE curriculum with the holistic development of students from the cognitive, affective and psychomotor perspectives. The impact of this UCE implementation can also be expressed in students. UCE is a program that emphasizes the concept of development and empowerment to produce future generations as true leaders. The program that has been collaborating with UGM has given the students the opportunity to directly participate in the project implementation on selected communities. Because of the observations found, based on the activities performed by the students have gone through each level for each specified domain. This has a positive impact on student development. Hence the concept of UCE can be used as a foundation in the development of the 3D Student Development Model concept framework.Â